2008
DOI: 10.1057/crr.2008.13
|View full text |Cite
|
Sign up to set email alerts
|

The Missing Link between Corporate Social Responsibility and Financial Performance: Stakeholder Salience and Identification

Abstract: In this paper, we present a framework for examining the relationship between corporate social responsibility (CSR) and firm financial performance. Ambiguity in empirical studies examining this relationship can be expected given both the ability and motivation of managers to focus their social responsibility initiatives on stakeholders with power, urgency and legitimacy. By considering the ability of stakeholders to reward or punish the firm based on their evaluations of the firm ' s activities, our model recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
141
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 62 publications
(52 reference statements)
5
141
1
4
Order By: Relevance
“…Vogel (2005) suggested that the EP-FP relationship depends on the context of the specific issue at hand because specific circumstances would alter the nature of the relationship. For example, the role of good management skills in translating good environmental actions to profits has been highlighted (Schuler and Cording 2006;Peloza and Papania 2008). The indirect impact of the role of industry sector has been highlighted by Lopez-Gamero et al (2009).…”
Section: The Case For More Complex Relationshipsmentioning
confidence: 99%
“…Vogel (2005) suggested that the EP-FP relationship depends on the context of the specific issue at hand because specific circumstances would alter the nature of the relationship. For example, the role of good management skills in translating good environmental actions to profits has been highlighted (Schuler and Cording 2006;Peloza and Papania 2008). The indirect impact of the role of industry sector has been highlighted by Lopez-Gamero et al (2009).…”
Section: The Case For More Complex Relationshipsmentioning
confidence: 99%
“…Previous research on the relationship between BSR and organizational performance found a numerous finding some reveals that positive, others negative and mixed or non-significant relation, those who reveals the positive relation includes (Griffin & Mahon, 1997;Peloza & Papania, 2008;Porter & Vander linde, 1995;Preston & V' Bannon, 1997;Rettab, Brik & Mellahi, 2009& Verschoor, 1998 while those indicate negative includes (Meznar et al, 1994;Vance, 1975& Wright & Ferris, 1997 and lastly, those who indicate mixed result include ( Berman et al, 1999;Cochran & Wood, 1984;Graves & Waddock, 1997;Hillman & Kein, 2001& McGuire, Sundegren, & Schneeweis, 1988. However, as noted earlier we cannot generalize the above finding because all the result comes from USA and Europe as against the developing nation.…”
Section: Bsr and Organizational Performancementioning
confidence: 97%
“…For many years a vast body of knowledge has emerged concerning the association between initiatives and organizational performance (Peloza & Papania, 2008). Despite all this attempt of research it suffers with major limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact will vary with the extent to which stakeholders expect firms to behave in a socially responsible manner, which varies considerably across countries (e.g., Chapple and Moon, 2005;Doh and Guay, 2006;Matten and Moon, 2008). Firms headquartered in institutional contexts that have greater expectations for socially responsible behavior are held to higher standards (Rowley and Moldoveanu, 2003) and face greater punishments if they fall short (Campbell, 2007;Peloza and Papania, 2008). Thus, firms in such contexts that fail to uphold their commitment to a self-regulatory program's objectives are at greater risk of provoking negative attention.…”
mentioning
confidence: 99%